Классификация методов обнаружения человеческих лиц - Пономаренко, Т. С. (My University, 2019)
Human face detection has always been an important problem for face, expression and gesture recognition. Face detection is the first and essential step for face recognition, and it is used to detect faces in the images. Face detection is a part of object detection and can use in many areas such as security, bio-metrics, law enforcement, entertainment, personal safety, etc. The given work describes faces detection methods based on their work principles, according to the classification by Yan, Kriegman, and Ahuja. The knowledge about how certain types of detection methods work provides the opportunity to choose the right one to accomplish given task.